2018
DOI: 10.3390/su10113849
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perceptions of Campus Sustainability Efforts: Lessons from Vermont

Abstract: Universities have begun to officially recognize advancing sustainability as an institutional goal. This paper reports on research on students’ awareness, attitudes, and behaviors at the University of Vermont as a means of understanding cultural acceptance of sustainability. We report on the results of a survey administered by an applied research methods class working in partnership with the University’s Office of Sustainability. Survey respondents report strong understanding of sustainability and believe it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…This is consistent with several studies that have explored actions taken by universities to promote environmentally sustainable food practices [22,42,43]. While there have been some positive steps taken in the U.S.A in particular, the implementation of initiatives has been piecemeal with few examples of universities that have adopted a comprehensive suite of actions [44,45].…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with several studies that have explored actions taken by universities to promote environmentally sustainable food practices [22,42,43]. While there have been some positive steps taken in the U.S.A in particular, the implementation of initiatives has been piecemeal with few examples of universities that have adopted a comprehensive suite of actions [44,45].…”
Section: Discussionsupporting
confidence: 82%
“…This is due to most scholars including context factors to describe the study background (e.g., [44,45]), usually to enhance transferability of the change approach taken. Several papers pointed out the importance of certain contexts to enable change, ranging from general recommendations (e.g., [46,47]) to the definition of success factors for specific interventions (e.g., [18,48]). Only four papers highlighted how context factors can impact organizational change.…”
Section: Contextmentioning
confidence: 99%
“…A shared understanding of what sustainability means in a HEI context is often seen as a basic prerequisite for organizational change [54,63]. Since sustainability is a highly ambiguous term with multiple potential interpretations [64], scholars suggest participatory approaches to enhance conceptual understanding and consensus-building [48,65]. A divergent point of view is put forward by Sylvestre et al [66], claiming that rather than trying to define sustainability in one way, a continuous dialogue and multiple visions of sustainability should be developed.…”
Section: Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, researchers found that faculties of science and engineering have the greatest changes in environmental attitudes and the highest level of sustainability knowledge based on a survey of 504 students from a Spanish university [11]. In the U.S., the authors of [12] studied students' awareness and attitudes at the University of Vermont and found a strong understanding of sustainability and that students consider sustainability to be important.…”
Section: Literature Reviewmentioning
confidence: 99%